Religiosity and Health-Related Risk Behaviours in a Secular Culture—Is there a Correlation? - Svensson, Nanna Herning (Journal of religion and health, 2020)
In the present study, we examine the correlation between religiosity and health-related risk behaviours among citizens aged 29-60 based on a cross-sectional survey in Denmark, known for its more secular culture. Health-related risk behaviours such as smoking and alcohol intake are known to increase the risk of developing one or more chronic or life-threatening diseases. In this study religiosity, in a random sample of Danes, seems to be associated with healthier lifestyle, such as a healthier dietary pattern and less smoking, as is found in more religious cultures. Our study suggests that religious practice among Danish citizens seems to be correlated with health behaviours and that healthcare professionals should pay more attention to the connection between religiosity and health.